Analisis Pemajasan Pada Lirik Lagu Band Nidji dan Penerapannya pada Pembelajaran Mengidentifikasi Unsur-unsur Puisi di SMA Kelas X - Nuryuliasih Nuryuliasih (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
The purpose of this study is to describe: (1) the figurative meanings contained in the lyrics of Nidji's song; (2) the imagery contained in the lyrics of the song Nidji; and (3) the application of Nidji's song lyrics in learning to identify the elements of poetry in class X SMA. The data collection of this research was carried out using the observation method. The data analysis of this research is content analysis. The results of data analysis are presented with informal techniques. Based on the data and discussion, it is concluded that (1) the figurative meanings contained in the lyrics of the Nidji song include (a) hyperbole figure of speech which serves to exaggerate the situation when someone is in love. His heart blossomed and everything became beautiful; (b) association figure of speech serves to describe different vibrations when falling in love with millions of feelings; (2) The types of imagery in Nidji's song lyrics consist of (a) auditory images found in the lyrics "I hear the singing of a thousand gods and goddesses of love" and "Echoing the world", (b) visual images found in the lyrics "I see the sun will come to me” and “I see the moon will come to me”, (c) the motion images found in the lyrics “Come to me, hug me dearly” and “The moon will come to me”. (3) The application of learning using Nidji's song lyrics is in accordance with basic competencies 3.17 Analyzing the elements of poetry building. The method used is Discovery Based Learning with learning steps which include the following: greeting and motivation, apperception, division of study groups, analyzing Nidji's song When I Fall in Love based on figurative and imagery elements, presentations, and concluding learning activities.